Design framework for mechanically intelligent bio-inspired grasper - Changoski, Vasko; Domazetovska Markovska, Simona; Jovanova, Jovana (Springer Science and Business Media LLC, 2025)
The challenge of designing real-world robots continues due to the complexities of navigating inaccessible terrains and encountering unexpected conditions. Introducing smart materials like shape memory alloys (SMAs) in the robot body can be beneficial due to their shape memory effect for actuation; however, there is no systematic way to introduce SMAs in a robot design. This research aims to address these challenges by proposing a design framework for SMA-actuated smart structures in robotic applications. Drawing inspiration from nature, the initial step in this framework involves conceptualizing a multifunctional grasper. This grasper utilizes SMA springs actuated by electric current, enabling various movements such as crawling, grasping, and folding. Analytical modeling is employed to determine the necessary characteristics of the SMA springs for one segment of the grasper. A multi-body modeling approach is utilized for more comprehensive understanding of the robot performance. This approach verifies the results of the analytical modeling and allows for performance optimization. Grasper’s dynamics is enhanced by fine-tuning actuation input signals, resulting in a more precise, sustainable, and energy-efficient grasper that is capable of traveling 400% longer distance than the initial concept design. The conducted experiments confirm that the proposed design framework for mechanically intelligent grasper has the potential to streamline the SMA-actuated structure design process by reducing development time, minimizing the trial-and-error iterations, and yielding cost savings in both development and prototyping phases.
Keywords: Multifunctional structure, Design framework, Bio-inspired, SMA materials, Optimization